A Never Ending Journey: Inclusive Education Is a Principle of Practice, Not an End Game. (September 2015) - Kozleski, Elizabeth B.; Yu, Ting; Satter, Allyson L.; Francis, Grace L.; Haines, Shana J.
A team from Schoolwide Integrated Framework for Transformation (SWIFT), a federally funded technical assistance project focused on creating cascading, aligned systems for inclusive education, conducted a series of focus groups and interviews with school administrators, general and special educators, and related service providers in six schools across the United States. Six themes merged from the study that highlighted the importance of defining inclusive education as well as building the capacity of people to understand and implement the components of a system of inclusive education. These themes suggest that leadership for inclusive education requires attention to the structures and processes used to signal that inclusive education is an undergirding principle of practice. Equally important is the development of relationships among students, teachers, and families that cement the structures. Networking, planning and organizing, using time and space strategically, and connecting schools with their communities were all aspects of capacity building. In addition, data revealed the importance of paying attention to the context of inclusive education within schools and in their surrounding communities. Further, enthusiastic support from and communication with families emerged as an important theme.